If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v = (50 + -2x)(30 + -2x) * x Reorder the terms for easier multiplication: v = x(50 + -2x)(30 + -2x) Multiply (50 + -2x) * (30 + -2x) v = x(50(30 + -2x) + -2x * (30 + -2x)) v = x((30 * 50 + -2x * 50) + -2x * (30 + -2x)) v = x((1500 + -100x) + -2x * (30 + -2x)) v = x(1500 + -100x + (30 * -2x + -2x * -2x)) v = x(1500 + -100x + (-60x + 4x2)) Combine like terms: -100x + -60x = -160x v = x(1500 + -160x + 4x2) v = (1500 * x + -160x * x + 4x2 * x) v = (1500x + -160x2 + 4x3) Solving v = 1500x + -160x2 + 4x3 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Simplifying v = 1500x + -160x2 + 4x3
| y-23=51 | | 56-2x=2x | | 5-1*x=19 | | (6+w)(2w-9)=0 | | Log[5](x+3)-log[5](x)=1 | | ydx-4xdy=y^6(dy) | | x^2+18x+c= | | 7a+6=15 | | L^2-45l=9000 | | ydx-4xdy=y^6 | | -(2x-3)(5x+4)= | | 3t+5x=10 | | (-2x+3)(5x+4)= | | ydx+(x+y^2)dx=0 | | -[3x-(2x+2)]=-7-[3(2x-4)-3x] | | -(2x+3)(5x+4)= | | 2f-1=13 | | 1-x*y=3 | | 3(2x+3)(7x+5)= | | 3(2x-3)(7x-5)= | | (0.5)(x/0.2)=2 | | (0.5)(x/0.2) | | 2-1*x=3 | | 6(2x+6)=12x | | (21x+4)(x+6)= | | (j-2)3=6j+8 | | 9x-(3x-7)=43 | | (7x-6)(3x-4)= | | 3k=9.75 | | x^3+3*x^2+4x+6=0 | | 2-10*x=0 | | 5=8/y-3 |